New Product Development : Easy-Peasy Box / Farah Hanisah Ibrahim ... [et al.] - Ibrahim, Farah Hanisah; Mohd Zulkifli, Farah Amani; Mohd Azahar, Nurul Aswani; Ishak, Umi Munirah (2021)
This study has been done to give an idea on how to apply technology solutions in real life based on what students learned about technology entrepreneurship. Nowadays, many people are bringing their homemade food to school or office. This is to make sure the food is healthy and clean. But the people like to use a disposable food container or use many items of container to store their food. Disposable food containers are very harmful to our environment and use many items of containers is very difficult to bring and handle. People also complain their food is not warm anymore when they want to eat during lunch. Therefore, in the New Product Development (NPD) study, we came up with an Easy-Peasy Box solution to this problem. This product is created with a combination of a lunch box and also a water bottle. This product is very convenient and compact for everyone since it comes with a pouch bag and adjustable strap. Easy-Peasy Box is manufactured using stainless steel to keep the food warm for up to 6 hours. Our target for this project is suitable for students, office workers, households, or travelers.